2021
DOI: 10.1111/ijcp.14060
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence to injectable glucagon‐like peptide‐1 (GLP‐1) receptor agonists dosed once weekly vs once daily in patients with type 2 diabetes: A meta‐analysis

Abstract: Background Suboptimal medication adherence has been associated with increased resource utilisation and mortality among patients with type 2 diabetes (T2D). Glucagon‐like peptide‐1 receptor agonists (GLP‐1RAs) are becoming increasingly important in the treatment of T2D. However, medications in this class differ considerably in their dosing frequency, which may impact adherence. We sought to perform a meta‐analysis to compare adherence to injectable GLP‐1RAs dosed once weekly vs once daily in patients with T2D. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 28 publications
2
29
0
1
Order By: Relevance
“…We suppose that decline in SMBG adherence over time might be one reason, while the possibility of reverse causality cannot be excluded. Our results, in conjunction with previous findings, 28‐30,32‐38 highlight the importance of maintaining SMBG adherence in patients with prolonged diabetes duration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We suppose that decline in SMBG adherence over time might be one reason, while the possibility of reverse causality cannot be excluded. Our results, in conjunction with previous findings, 28‐30,32‐38 highlight the importance of maintaining SMBG adherence in patients with prolonged diabetes duration.…”
Section: Discussionsupporting
confidence: 90%
“…We suppose that decline in SMBG adherence over time might be one reason, while the possibility of reverse causality cannot be excluded. Our results, in conjunction with previous findings, [28][29][30][32][33][34][35][36][37][38] highlight the importance of maintaining SMBG adherence in patients with prolonged diabetes duration. Interestingly, we observed that SMBG was independently associated with hypoglycemia in both study populations.…”
Section: Ta B L E 2 Association Between Smbg and Hba1c < 7%supporting
confidence: 90%
“…Of note, GLP-1 RA and DPP-4 inhibitors including exenatide, liraglutide, sitagliptin, vildagliptin, and saxagliptin, were only licensed in Italy sometime after the study start and were not included in the diabetes medication algorithm. As a result, it cannot be excluded that, if investigators were provided with additional new-generation drugs with high efficacy [15], low hypoglycemia risk, lower frequency of administration [16,17], and/or cardiovascular/renal benefits [18][19][20], this could affect their attitude to review patients' therapy and, in turn, short-term glycemic outcomes. Moreover, different patient characteristics or different SMBG testing schemes may lead to different results.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a population-based analysis in the UK estimated a median delay to insulin initiation of 4.9 years and 4.2 years for patients with HbA 1c levels of ≥8.0% and ≥9.0%, respectively [33]. Clinical inertia on the part of either clinicians or their patients has been attributed to concerns related to hypoglycemia and weight gain, fear of injections, and anticipation of problems with treatment adherence and a reduced quality of life [31,32,[34][35][36][37][38][39][40][41]. Technological advances (e.g., in formulations and devices) have addressed some of these concerns, and many can be managed through education and support [32,42]; as such, these concerns may often be unwarranted.…”
Section: Rationale For Developing Once-weekly Basal Insulin Replacement Therapymentioning
confidence: 99%
“…If a basal insulin could be injected just once weekly, it is reasonable to predict that this would reduce clinical inertia, increase treatment adherence, and improve patients' quality of life, provided that the risk of hypoglycemia remains low. It is reasonable to extrapolate such assumption from the comparisons of once-weekly GLP-1 RAs with once-daily GLP-1 RAs that are encouraging in this regard [38][39][40][41].…”
Section: Rationale For Developing Once-weekly Basal Insulin Replacement Therapymentioning
confidence: 99%